Najnowsza historiografia hiszpańska na temat pogranicza chrześcijańsko-muzułmańskiego na Półwyspie Iberyjskim w XIII-XV wieku - Malinowski, Mariusz (Acta Universitatis Lodziensis. Folia Historica, 2001)
The late Middle Ages, which means for Spain the period closed between 1212 (dale of the victory in Las Navas de Tolosa), or 1248 (the conquest of Seville) and the death of Isabel the Catholic (1504) or that of her husband (1516) is one of the most classical epoch in the Spanish history. According to the commonly shared opinion, between XIIIth and XVIth century was born this Spain which exists nowadays. The late Middle Ages created the base for the „hispanity”, whose culmination could be seen during the conquest of America, when the Spanish men used to make famous for all over the world los usos de Castilla y de León. The border between kingdoms of Castille and Aragon and the emirate of Granada was in big part the forge of the Spanish national consciousness. Actual Spanish historiography apports some notes to the description of the people who lived in Iberic frontiere in the late Middle Ages. First, we can see a man whose life is closely united with the war realities. That is, moreover, why we can see almost exclusively men, not women. Presented books and articles show us a man living in permanent tension and fear towards the assault of the Granadian troops. Assault which could finish with his own or his family s death. Very often such events used to be done in order to captive people and animals. Both parts of the border between Castille and Aragon with Granada are today integral part of Spain. Although we are able to define some characteristics of the habitant of Seville, Cordoba or Valencia, by extending some observations to the people from Granada, Malaga or Almeria we would take a big risk. And the reason is that the Spanish historiography dedicate much more space for men from Castille and Aragon that those of the emirate. Apart of some difficulties in the access to sources in Arabic, there are another, and much more important circumstances determining that state of things. According to great part of Spanish historiography, the „hispanity” is European, Christian, and not Muslim. Actual Spain seeks her origins in Castille, Aragon, or Navarra (incorporated in 1512). And it seems very compatible with the ofllcial Spanish policy of today. After all, the alternative would be the necesily of admit that between Spanish relatives there are a place for Marocco, the nearest and perhaps the unique candidate for the heritage of the millenary Islam’s presense on the peninsula. The discussion about the role of the Muslim period for Spain supports the theory of her „occidental” origin. And the Orient must wait...